IMPACTO NA QUALIDADE DE VIDA RELACIONADA A SAÚDE BUCAL EM GESTANTES - Bolsson, Gabriela Bohrer (2017)
Objective: The purpose of the present study was to verify the factors that affect the quality of life related to oral health (HRQoL) of pregnant women, attended at the Basic Health Units and Family Health Strategies, in the municipality of Santa Maria, Rio Grande do Sul. South. Material and Method: The study design was of a cross-sectional type, of which 100 pregnant women participated in this study. Information regarding the QVRSB of pregnant women was collected through the Oral Health Impact Profile (OHIP-14). Data related to biological characteristics, socioeconomic factors and social support were obtained through a semi-structured questionnaire. Results: Descriptive analysis showed that the mean gestation time was 27.6 weeks; 75.8% of the participants were single and only 21.2% had a family income less than two minimum wages. In addition, the majority of pregnant women were in the age group between 20 and 30 years of age, with the mean age being 24.6 years. Still, 53% declared themselves white and 55% did not work. Regarding clinical dental conditions, most of the pregnant women had depth of probing (PS) ≥ 3mm and clinical insertion level (NIC) ≥ 3mm and the mean CPO-S was 12.77 (SD: 15.16). Regarding the impact on the HRQoL, the mean OHIP-14 score was 2.5 (dp: 1.3), with the domains most affected: disability followed by the domain of psychological discomfort and social disability. After the Poisson-adjusted analysis, it was observed that pregnant women older than 40 years were 47% more likely to report an impact on the HRQoL compared to those <20 years of age. White women showed a lower impact on the QVRSB when compared to black, brown or indigenous women. In addition, women with more than 8 years of schooling have a protective factor when compared to those with less schooling. Regarding social support, pregnant women who never or almost never had someone to give information had a greater impact on the quality of life related to oral health. Clinical data on caries and periodontal disease did not have an impact on HRQoL in the sample evaluated. Product: As a product of this Master's Dissertation, didactic material was built, based on a virtual learning technology, about prenatal dentistry and its importance for the pregnant woman and her baby. Conclusion: health education is essential to prenatal dentistry, since the quality of life related to the oral health of the pregnant woman will have repercussions on her general health and that of her baby.